The Significance of Psychosocial Well-Being for Trauma Healing in Randa Abdel-Fattah’s Where The Streets Had a Name - Aulia, Lisa (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2021)
This paper elaborates an in-depth research on the novel Where the Streets Had a Name. This research aims to analyze trauma as the impact of Palestinian-Israeli conflict to Hayaat. Hayaat a Palestinian that is exposed to traumatic memory end up coping with her traumatic memory in the conflicting country, and Hayaat finds one of her trauma healing from Israelis as the party that threatens and intimidates Palestinians. Trauma is a psychological injury which is caused by emotional shock. As this research uses the qualitative method, this research aims to explain trauma healing on Hayaat. To analyze the change that Hayaat experience because of trauma, this research uses trauma theory by Nigel C. Hunt. The theory discusses how trauma emerges traumatic symptoms such as intrusive recollections, avoidance, negative emotions and thoughts, and hyperarousal to traumatized people. The theory brings a solution up to help traumatized people to cope with trauma. By the presence of psychosocial well-being, Hayaat successfully cope with her trauma. [Penelitian ini meneliti novel Where the Streets Had a Name dengan tujuan untuk menganalisis dampak atas konflik Palestina-Israel terhadap Hayaat. Hayaat adalah orang Palestina yang terpapar kejadian traumatis dan berhasil sembuh dari trauma di negara yang sedang berkonflik. Ia disembuhkan oleh orang-orang Israel yang selama ini mengancam dan mengintimidasi orang-orang Palestina. Trauma merupakan penyakit kejiwaan yang disebabkan oleh emosi yang terguncang. Sebagai sebuah penelitian kualitatif, penelitian ini bertujuan untuk menjelaskan penyembuhan trauma terhadap Hayaat. Untuk menganalisis trauma yang dialami Zeynab, penelitian ini menggunakan teori trauma oleh Nigel C. Hunt. Teori tersebut membahas bagaimana trauma memunculkan simtom-simtom trauma seperti ingatan yang menggangu, pengabaian, emosi dan pikiran negatif, serta perubahan emosi serta tingkah laku terhadap orang-orang yang menderita trauma. Teori tersebut menyuguhkan solusi atas trauma yang dialami oleh penderita. Kehadiran psikososial membantu Hayaat untuk mengatasi trauma yang ia alami.]